Effectiveness of Water Hyacinth Bioconversion and Fermented Fruit Waste as a Growing Media Larvae of Hermetia illucens - Wahyuni; R. C. Fadhlil (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2022)
Black Soldier Fly (BSF) larvae have cellulosic activity in the presence of bacteria in their intestines. Generally, the organisms that play a role in bioconversion process are bacteria, and Hermetia illucens larvae as a bioconversion agent for fermented water hyacinth are combined with fruit waste and used as a growth medium. The purpose of this study was to determine the increase in larva mass weight, feed conversion efficiency, waste reduction index from water hyacinth bioconversion activity and fermented fruit waste by Hermetia illucens larvae. Hermetia illucens larvae are treated with feeding P0 = 100 % fruit waste, P1 = Fruit waste 25 % + 75 % fermented water hyacinth, P2 = 50 % fruit waste + 50 % fermented water hyacinth, and P3 = 75 % fruit waste + 25 % fermented water hyacinth. The larvae used were 6 days old, for all treatments 50 g used. The results showed that P3 = 75 % fruit waste + 25 % fermented water hyacinth produced the highest average final mass weight of larvae, namely 124.62 g, average feed consumption was 72.72 %, average ECD and WRI values were 10.98 % and 10.38 %, respectively. The mixing level of water hyacinth and fermented fruit waste in treatment 3 showed effective results as a medium for the growth of Hermetia illucens larvae.